2018
DOI: 10.37358/rc.18.6.6331
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Behaviour of Polyester Nanocomposites with Graphene Oxide and Graphite Investigated Through Block-on-ring Test

Abstract: A new class of polyester nanocomposites with graphene oxide and graphite has been obtained through a specific chemical method. Aiming to assess the tribological performance of this type of material, a basic experimental plan has been conceived which includes block-on-ring test, wear rate measurement, Vickers micro hardness test and scanning electron microscopy. Accordingly, the influence of graphene oxide and graphite on coefficient of friction and friction stability were investigated through wear test of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In this way, mass loss is reduced compared to pure polyester coating. Similar results were observed for polyester nanocomposites with graphene oxide and graphite (BASTIUREA et al, 2018). Adapted from Gafsi et al (2021).…”
Section: Go Reinforced Polyester Nanocompositessupporting
confidence: 76%
See 1 more Smart Citation
“…In this way, mass loss is reduced compared to pure polyester coating. Similar results were observed for polyester nanocomposites with graphene oxide and graphite (BASTIUREA et al, 2018). Adapted from Gafsi et al (2021).…”
Section: Go Reinforced Polyester Nanocompositessupporting
confidence: 76%
“…Furthermore, the macromolecular chains of nanocomposites tend to be stiffer than those of pure polyester when subjected to deformation, leading to a better wear resistance property. Furthermore, the thermal conductivity of GO can be beneficial when it comes to transferring frictional heat, which leads to a reduction in the decomposition of polyester resin in the friction area (BASTIUREA et al, 2018;BASHANDEH et al, 2019;ZHAI et al, 2017). In order to identify the wear mechanisms, the authors made SEM observations of the wear track on the coating surface of the GO-reinforced nanocomposites after 10.000 sliding cycles.…”
Section: Go Reinforced Polyester Nanocompositesmentioning
confidence: 99%
“…(2) Polyester-type A new class of polyester nanocomposites with GO was obtained via a specic chemical method. 106 Through the wear test of the nanocomposite block on the steel ring, it was concluded that the incorporation of GO nanosheets into the polyester matrix at very low levels resulted in signicantly altered tribological properties. The inclusion of GO in the polyester matrix resulted in better anti-wear behavior of the nanocomposite.…”
Section: Graphene-polymer Nanocompositesmentioning
confidence: 99%